A model experiment on nano-particle stability in 12Cr-ODS steel using high-resolution high voltage microscopy. (July 2022) - Zhang, Yifan; Li, Ranran; Diao, Sizhe; Han, Wentuo; Yoo, Seung Jo; Ohnuki, Somei; Zhan, Qian; Wan, Farong
Abstract: In this work, the microstructure stability of 12Cr-ODS ferritic steel under irradiation is studied using a high-resolution high voltage electron microscope up to 1.5 dpa at 300 and 500 °C. Coherent YTiO3 nanoparticles (NPs) undergo coarsening during electron irradiation and the coarsening rate is positively correlated to irradiation temperature (the third power of NPs size is proportional to the irradiation dose). He pre-implantation can significantly reduce the coarsening rate. A model coupling Ostwald ripening and irradiation enhanced diffusion is used to explain this coarsening. The fitting results between NPs size and irradiation dose show that pre-implanted He causes a lower diffusion of Y in 12Cr-ODS steel compared with the non-implanted sample. In response to the irradiation, plate-like radiation-induced precipitates appear which result in diffraction streaks in fast fourier transform (FFT) pattern. Precipitations are paralleled to [100] or [110] direction of Fe matrix and located near the interface between NPs and matrix. The hypothesis that coherent Cr precipitate along NPs/matrix interface caused diffraction streaks is proposed. Besides, He pre-implantation can also delay this precipitation. Graphical abstract: Image, graphical abstract